Dissecting the key genomic regions underlying high yield potential in common wheat variety ‘Kenong 9204’ - Chun-hua ZHAO; Na ZHANG; Xiao-li FAN; Jun JI; Xiao-li SHI; Fa CUI; Hong-qing LING; Jun-ming LI (Journal of Integrative Agriculture, 2023)
The foundation parents play key roles in the genetic improvement of both yield potential and end-use quality in wheat. Characterizing the genetic basis that underlies certain beneficial traits in the foundation parents will provide theoretical reference for molecular breeding by a design approach. ‘Kenong 9204’ (KN9204) is a candidate foundation parent characterized by ideotype, high yield potential, and particularly high nitrogen fertilizer utilization. To better understand the genetic basis of its high yield potential, high throughput whole-genome re-sequencing (10×) was performed on KN9204, its parental lines and its derivatives. A high-resolution genetic composition map of KN9204 was constructed, which showed the parental origin of the favorable genomic segments based on the identification of excellent yield-related quantitative trait loci (QTL) from a bi-parental mapping population. Xiaoyan 693 (XY693), a wheat–Thinopyrum ponticum partial amphidiploid, contributed a great deal to the high yield potential of KN9204, and three major stable QTLs from XY693 were fine mapped. The transmissibility of key genomic segments from KN9204 to its derivatives were delineated, indicating that haplotype blocks containing beneficial gene combinations were conserved along with directional selection by breeders. Evidence for selection sweeps in the breeding programs was identified. This study provides a theoretical reference for the breeding of high-yield wheat varieties by a molecular design approach.